Pressures for sustainability and strategic responses on employment relationships: The role of the HR manager - Mar Bornay-Barrachina; Jaime Guerrero-Villegas; Macarena López-Fernández; Margarita Ruiz-Rodríguez (European Research on Management and Business Economics (ERMBE), 2023)
The study objective was to show how a company's internal factors, such as organizational commitment and HR manager role can affect the establishment of different employment models towards sustainability. Specifically, we defined a model that analyses how an organisation's external (Institutional Pressures for Sustainability, or IPS) and internal factors (Sustainable Strategic Commitment, or SSC) can influence a company's Employment Relationships (ERs)- i.e., the relationships between employers and employees. We tested our hypotheses on a sample of 145 Spanish companies conducting multiple regression analyses as well as the moderation and mediation test using PROCESS (for SPSS v3.5). The results showed that despite the direct influence of IPS on ERs, a company's commitment and/or contribution towards sustainability plays a major role, as the latter constitutes the mechanism through which IPS enhance ERs. Furthermore, our results confirm the HR manager's significant role in fostering a company's strategic commitment to sustainability, thereby reinforcing the relationship between IPS and SSC. Consequently, HR management can develop a set of ERs better suited to a sustainable model, that is, one which encourages long-term commitment (Mutual Investment).
Keywords: M10; M14; M51; 650; Institutional pressures for sustainability; Sustainable strategic commitment; Employment relationships; HR manager's role